2023
DOI: 10.1039/d3nh00090g
|View full text |Cite
|
Sign up to set email alerts
|

Intervalley scattering induced significant reduction in lattice thermal conductivities for phosphorene

Abstract: Thermal transport properties of buckled phosphorene (β-P) and antimonene (β-Sb) are investigated using first-principles methods. The large acoustic-optical phonon gap of 3.8 THz and 2.2 THz enable the four-phonon interaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…As opposed to the ideal cubic perovskite, BaZrS 3 is isostructural with GdFeO 3 and adopts the twisted perovskite structure with the orthorhombic phase . Studies have shown that the reduction of symmetry can significantly reduce the phonon degeneracy and enhance the avoid-crossing behavior of phonon branches, which result in an increase in the phonon–phonon scattering phase space to limit lattice thermal transport. Using T = 0 K force constants, the lattice thermal conductivity of BaZrS 3 at 300 K is calculated to be as low as 1.16 W/mK on the basis of the iterative solution of the Boltzmann transport equation (BTE) . However, in this scheme, the temperature effect affects only the Bose–Einstein distribution of phonons, and its effects on phonon dispersion, phonon–phonon interaction, and electron–phonon interaction are completely ignored, which may lead to the misestimation of thermal conductivity .…”
mentioning
confidence: 99%
“…As opposed to the ideal cubic perovskite, BaZrS 3 is isostructural with GdFeO 3 and adopts the twisted perovskite structure with the orthorhombic phase . Studies have shown that the reduction of symmetry can significantly reduce the phonon degeneracy and enhance the avoid-crossing behavior of phonon branches, which result in an increase in the phonon–phonon scattering phase space to limit lattice thermal transport. Using T = 0 K force constants, the lattice thermal conductivity of BaZrS 3 at 300 K is calculated to be as low as 1.16 W/mK on the basis of the iterative solution of the Boltzmann transport equation (BTE) . However, in this scheme, the temperature effect affects only the Bose–Einstein distribution of phonons, and its effects on phonon dispersion, phonon–phonon interaction, and electron–phonon interaction are completely ignored, which may lead to the misestimation of thermal conductivity .…”
mentioning
confidence: 99%